2012
DOI: 10.1074/jbc.m112.403584
|View full text |Cite
|
Sign up to set email alerts
|

Keratin K18 Increases Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Surface Expression by Binding to Its C-terminal Hydrophobic Patch

Abstract: Background: CFTR function is tightly regulated by many interacting proteins. Results: Intermediate filament protein keratin 18 increases the cell surface expression of CFTR by interacting with the C-terminal hydrophobic patch of CFTR. Conclusion: K18 controls the function of CFTR. Significance: These findings offer novel insights into the regulation of CFTR and suggest that K18 and its dimerization partner, K8, may be modifier genes in cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Since DRA is a central intestinal Cl Ϫ /HCO 3 Ϫ transporter, the nearly complete loss of DRA in the K8 Ϫ/Ϫ colon described here, together with the upregulation and mistargeting of AE1/2 (39), explains the decreased Cl Ϫ uptake. No major differences in mRNA levels for PAT-1 or CFTR were observed; however, a role for K8/K18 in CFTR function cannot be ruled out, since K18 was recently found to bind CFTR and regulate CFTR localization to the membrane (8). Indeed, in K18 Ϫ/Ϫ (8) and K8 Ϫ/Ϫ (2) small intestine villi (but not crypts), CFTR surface expression was reduced.…”
Section: Discussionmentioning
confidence: 92%
“…Since DRA is a central intestinal Cl Ϫ /HCO 3 Ϫ transporter, the nearly complete loss of DRA in the K8 Ϫ/Ϫ colon described here, together with the upregulation and mistargeting of AE1/2 (39), explains the decreased Cl Ϫ uptake. No major differences in mRNA levels for PAT-1 or CFTR were observed; however, a role for K8/K18 in CFTR function cannot be ruled out, since K18 was recently found to bind CFTR and regulate CFTR localization to the membrane (8). Indeed, in K18 Ϫ/Ϫ (8) and K8 Ϫ/Ϫ (2) small intestine villi (but not crypts), CFTR surface expression was reduced.…”
Section: Discussionmentioning
confidence: 92%
“…The IFs: K8 and keratin 18 (K18) prevent the delivery of functional ΔF508‐CFTR to the plasma membrane . K18 reportedly binds to the CFTR C‐terminus, regulating its function . We recently demonstrated that K8, but not K18, physically binds to the NBD1 of both wt and ΔF508 CFTR, with a greater tendency to target the unfolded destabilized conformation caused by F508 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Other molecules such as curcumin or resveratrol derived from plants may act by modifying keratin 18 (K18) network (Hamdaoui et al, ; Lipecka et al, ). K18 heterodimerizes with keratin 8 (K8) and further evidence suggests that both proteins play a role in the trafficking of CFTR/ΔF508‐CFTR (Colas et al, ; Duan et al, ). Accordingly, we have reported that a decrease in K8 expression leads to functional correction of ΔF508‐CFTR (Colas et al, ).…”
Section: Introductionmentioning
confidence: 99%